RESERVATION SYSTEM WITH THE PAN AMERICAN ROUND AND CASES RESERVATIONS ON 1951 GENOCIDE CONVENTION - Yaya Kareng; Hartanto Hartanto; Choirul Anam (International Journal of Law Reconstruction, 2019)
A reservation is a unilateral statement made by a State at the time of signing, accept, ratify, ratify or accede to the treaty, which is the main content is to issue or to modify the legal effect of certain provisions in its enforcement against the State (KW 1969). Initially reservation (requirements) are defined differently based subjects that provide definition. As for the definition independent of the reservation that in general it is a unilateral statement put forward by a country at the time expressed consent to be bound by a treaty, which said "Refuse to accept or recognize or do not want to be tied to, or unwilling to accept the legal consequences of one or more provisions of the agreement, or to modify or customize the content or provide its own meaning on one or more provisions of the agreement in accordance with the needs of the country ", dissent is possible if there is no commonly agreed definition.